"Educational Challenges and Solutions for International Students in Korea" (Journal of Pedagogical Inventions and Practices, 2024)
International students studying in Korea face significant challenges such as language barriers, high academic pressure, and social integration issues. These challenges negatively impact their academic performance, mental health, and overall well-being. This paper explores the obstacles faced by international students and offers suggestions to support them. Specifically, it emphasizes the need for improving mental health support systems, enhancing language learning programs, and promoting social integration. Additionally, the paper discusses the possibilities of using 3D Figma platforms to address these issues. Through 3D modeling and interactive learning tools, international students can improve their academic skills, better understand complex materials, and effectively engage in language learning processes. This approach also strengthens mental health support and facilitates social integration, creating a supportive environment for international students in Korea.